Analysis of Social Capital Determinants on the Level of Community Income Increase in Tourism Villages: Bonjeruk Village - Winda, Baiq; Agustiani, Eka (International Journal of Economics Development Research (IJEDR), 2024)
The development of tourist villages depends on the involvement of local communities and their social capital relationships. Social capital describes social life in which people collaborate to increase income. On the other hand, Bonjeruk Village has not succeeded in utilizing its social capital effectively to build and develop its potential. The aim of this research is to study how social capital impacts the income level of people in Bonjeruk Village. Social capital, which consists of the components of social networks, participation, norms, and trust, plays an important role in rural economic development. This study used an associative quantitative approach and involved one hundred respondents with random sampling. Data analysis used the SEM-PLS 4 program. Structural equation model analysis was used to evaluate the relationship between variables. The research results show that the level of participation, social networks and norms in Bonjeruk Village are very positive. However, in contrast to the trust variable in Bonjeruk Village, it is still low, which shows the relationship between social capital and community income. The results show that increasing trust in society is an important component of social capital.